Actinobaculum schaalii: An Emerging Uropathogen?. (9th April 2012) - Tavassoli, Peyman; Paterson, Ryan; Grant, Jennifer
Abstract : A. schaalii is a rare uropathogen. We report urosepsis with Actinobaculum schaalii detected serendipitously in blood and urine culture in a 79-year-old with urinary tract obstruction. This paper illuminates the flaws in our current system in detecting A. schaalii and raises awareness among clinicians and laboratory teams.